2023
DOI: 10.1155/2023/8191261
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Machine Learning Techniques (MLT) for Heart Disease Prediction

Abstract: The leading cause of death worldwide today is heart disease (HD). The heart is recognised as the second-most significant organ behind the brain. A successful outcome of treatment can be improved by an early diagnosis which can significantly reduce the chance of death in health care. In this paper, we proposed a method to predict heart disease. We used various machine learning algorithms (MLA), namely, logistic regression (LR), k-nearest neighbor (KNN), support vector machine (SVM), Naive Bayes (NB), random for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Experiments showed that random forest had the highest accuracy rate of 98%, followed by multi-layer perceptron (90.99 %), Support Vector Machines (92%), Gradient Boosting (97%), Decision Trees (96%), and Logistic Regression (69%). This is similar to the findings of heart disease risk prediction studies ( Ansari et al, 2023 ). Shahadat et al ( Uddin et al, 2022 ) considered 31 disease-related variables and conducted an analysis based on the guidelines of the Elixhauser Comorbidity Index.…”
Section: Introductionsupporting
confidence: 90%
“…Experiments showed that random forest had the highest accuracy rate of 98%, followed by multi-layer perceptron (90.99 %), Support Vector Machines (92%), Gradient Boosting (97%), Decision Trees (96%), and Logistic Regression (69%). This is similar to the findings of heart disease risk prediction studies ( Ansari et al, 2023 ). Shahadat et al ( Uddin et al, 2022 ) considered 31 disease-related variables and conducted an analysis based on the guidelines of the Elixhauser Comorbidity Index.…”
Section: Introductionsupporting
confidence: 90%
“…One of the essential keys that has a direct impact on classification performances is the feature selection technique [ 39 ]. Feature selection eliminates unnecessary data by removing the less relevant features [ 40 ]. Many feature selection types, such as ReliefF, mutual information, and embedded methods like Lasso and Ridge, work well to reduce the number of features during classification.…”
Section: Review Of Literaturementioning
confidence: 99%